Response of Montane Fish Biodiversity to Landscape and Anthropogenic Activity Under Potential Water Quality Pathways - Wenjun Zhong; Wanjuan Bi; Yan Zhang; Feilong Li; Zehua Zhang; Xiangyun Huang; Xunjie Liu; Yifan Wang; Song Zhang; Shan Xu; Loïc Pellissier; Xiaowei Zhang (Ecology and Evolution)
ABSTRACT Mountain river ecosystems, globally recognized biodiversity hotspots shaped by pronounced landscape heterogeneity, are facing intensifying anthropogenic pressures. However, interactions between landscape and anthropogenic activity on montane fish biodiversity remain poorly quantified. Taking the Yuan River (Yunnan, China) as a model system, environmental DNA (eDNA) and partial least squares structural equation modeling (PLS‐SEM) were coupled to disentangle responses of fish biodiversity facets (taxonomic, functional and genetic diversity) to elevation and human footprint gradients. First, eDNA‐derived taxonomic composition (R = 0.97 against catch data) demonstrated Cypriniformes and Perciformes dominance. Second, downstream areas exhibited enhanced taxonomic (R = 0.32) and functional diversity (R = 0.49), contrasting with upstream genetic diversity maxima (R = −0.47). Third, elevation gradients and human footprint exerted stronger direct effects on taxonomic diversity than on functional or genetic metrics, independent of spatial autocorrelation. Crucially, PLS‐SEM identified water quality (i.e., total phosphorus (TP), total nitrogen (TN), biochemical oxygen demand (BOD5), and total organic carbon (TOC)) as a pivotal mediator linking elevation and human footprint to biodiversity outcomes. Overall, the present study establishes a mechanistic framework for disentangling landscape and anthropogenic drivers of biodiversity change, offering a scalable reference for conservation prioritization in montane freshwater ecosystems.